(untitled) (DAPesquisa, 2021)
In this article, we analyze the works of Gordon Matta-Clark and Michael Wesely from a fragmented visuality which began with the relationship between the subject and the camera obscura. Based on the discontinuous and unstable vision of the observer, conceptualized and reported by Jonathan Crary, we investigate how both artists use photography as a way of disaggregating the limits which are set between past and present, so that space and time become undetermined. Thus, we appropriate the writings of Walter Benjamin, Maurice Blanchot and Jacques Derrida on ruins to study the way photographic image asserts itself as lacerated configurations, by opening itself, through superimpositions, ramifications and excesses, as obliterated and incomplete representations.